Training on Sharia-Compliant Slaughtering of Livestock and Poultry for Youth in Giriwondo Village - Gunawan, Herri; Faqih, Muhammad Abdullah; Ciptaning, Arsala Haq Hamengku; Musa, Andi Zulfikar (Jurnal Pengabdian Masyarakat, 2025)
Purpose: To educate the youth of Giriwondo Village on the etiquette and procedures of sharia-compliant slaughtering of livestock and poultry. Method: The approach used in this training includes convincing the community and parents to accept the inevitability of generational succession and motivating young people to overcome their fear of slaughtering livestock and poultry. The technical implementation involves the role of the youth organization leader in coordinating the participants. Practical Application: Adolescent youths have the potential to become professional butchers in Giriwondo Village or at least be able to perform independent slaughtering after gaining knowledge from this training. Conclusion: The youth are willing to accept, listen to, and understand the theoretical explanations presented in the training.